Overall performance assessment of a combined cycle power plant: An exergo-economic analysis. (15th May 2016) - Sahin, Ahmet Z.; Al-Sharafi, Abdullah; Yilbas, Bekir S.; Khaliq, Abdul
Highlights: An exergo-economic analysis is carried out for a combined cycle power plant. An overall performance index (OPI) is defined to analyze the power plant. Four performance indicators and three scenarios are considered in the analysis. The optimum configuration of the power plant differs for each scenarios considered. Abstract: An exergo-economic analysis is carried out for a combined cycle power plant using the first law and the second law of thermodynamics, and the economic principles while incorporating GT PRO/PEACE Software Packages. An overall performance index (OPI) is defined to assess and analyze the optimum operational and design configurations of the power plant. Four performance indicators are considered for the analysis; namely, energy efficiency (ENE), exergy efficiency (EXE), levelized cost of electricity (COE), and the total investment (TI) cost. Three possible scenarios are considered in which different weight factor is assigned to the performance indicators when assessing the performance. These scenarios are: (i) the conventional case in which the levelized cost of electricity is given a high priority, (ii) environmental conscious case in which the exergy efficiency is given a high priority, and (iii) the economical case in which the total cost of investment is given a high priority. It is shown that the optimum size and the configuration of the power plant differ for each scenarios considered. The selection and optimization of the size and configuration of the power plant are found to be depending on the user priorities and the weight factors assigned to the performance indicators.